The Basic Words and Terms of Sport Games and Motions in the Holy Quran : semantic study (Journal of the College of Education for Women, 2019)
(( The Basic word and Terms of sports, games and motions in the Holy Quran : semanticstudy )).The research consists of apreface followed by an Introduction , and three sections andaconclusion, finally the research concluded with a list of the sources . and also alist of termsand word in English language for a wider use .As for reach sections, they are section one it covers a group of words sports games thatare forty two words .Section two : it covers five fields :-a- A group of words ( sports ruless) that an seventeen words.b- A group of ( sports montions ) that are ten .c- A group of ( sports tools ) that are seven words.d- A group of ( sports sciences ) that are seven words only .e- A group for (especial cases ) that has one word .Section three : it consists of semantic phenomena for words and basic terms of sports gamesand motions in the Holy Quran . for instances :- synonymy, Homongm Oxymoron thissection also consists of semantic words between original stem and sport term . also semanticgenerality and especially of some words in sports roundings.